Sound Thinking and Its Relation to Meta-mood: Educational Counselors in Schools: Pemikiran yang Rasional dan Hubungannya dengan Meta-mood: Konselor Pendidikan di Sekolah - Al-Mayahy, Rawaa Jaafar Abd; Al-Anzi, Hussein Karim Mohammed (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Positive thinking is a central construct in psychological well-being, closely associated with emotional regulation and adaptive cognitive processes. Specific Background The integration of emotional intelligence and meta-mood concepts has provided a theoretical basis for understanding how individuals monitor and manage their emotional states. Knowledge Gap Despite extensive theoretical development, there remains limited clarity in linking positive thinking constructs with measurable emotional regulation mechanisms in educational and psychological contexts. Aims This study aims to examine the relationship between positive thinking and meta-mood components, focusing on emotional attention, clarity, and repair. Results The findings indicate a significant association between positive cognitive patterns and improved emotional awareness, regulation, and psychological balance. Novelty The study contributes a conceptual integration of positive thinking with meta-mood dimensions, offering a structured perspective on emotional regulation processes. Implications The results provide a theoretical basis for developing educational and counseling strategies that support emotional awareness and cognitive resilience Keywords: Positive Thinking, Meta Mood, Emotional Regulation, Emotional Intelligence, Cognitive Processes Key Findings Highlights Cognitive patterns correlate with awareness and management of emotional states Emotional clarity supports stability in psychological responses Integrated framework links cognition with affective processing